The repetitive DNA landscape in Avena (Poaceae): chromosome and genome evolution defined by major repeat classes in whole-genome sequence reads - Liu, Qing (BMC Plant Biol, 2019)
BACKGROUND: Repetitive DNA motifs – not coding genetic information and repeated millions to hundreds of times – make up the majority of many genomes. Here, we identify the nature, abundance and organization of all the repetitive DNA families in oats (Avena sativa, 2n = 6x = 42, AACCDD), a recognized health-food, and its wild relatives. RESULTS: Whole-genome sequencing followed by k-mer and RepeatExplorer graph-based clustering analyses enabled assessment of repetitive DNA composition in common oat and its wild relatives’ genomes. Fluorescence in situ hybridization (FISH)-based karyotypes are developed to understand chromosome and repetitive sequence evolution of common oat. We show that some 200 repeated DNA motifs make up 70% of the Avena genome, with less than 20 families making up 20% of the total. Retroelements represent the major component, with Ty3/Gypsy elements representing more than 40% of all the DNA, nearly three times more abundant than Ty1/Copia elements. DNA transposons are about 5% of the total, while tandemly repeated, satellite DNA sequences fit into 55 families and represent about 2% of the genome. The Avena species are monophyletic, but both bioinformatic comparisons of repeats in the different genomes, and in situ hybridization to metaphase chromosomes from the hexaploid species, shows that some repeat families are specific to individual genomes, or the A and D genomes together. Notably, there are terminal regions of many chromosomes showing different repeat families from the rest of the chromosome, suggesting presence of translocations between the genomes. CONCLUSIONS: The relatively small number of repeat families shows there are evolutionary constraints on their nature and amplification, with mechanisms leading to homogenization, while repeat characterization is useful in providing genome markers and to assist with future assemblies of this large genome (c. 4100 Mb in the diploid). The frequency of inter-genomic translocations suggests optimum strategies to exploit genetic variation from diploid oats for improvement of the hexaploid may differ from those used widely in bread wheat. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-019-1769-z) contains supplementary material, which is available to authorized users.